CISMeF: A Structured Health Resource Guide - Darmoni, S. J.; Leroy, J. P.; Baudic, F.; Douyère, M.; Piot, J.; Thirion, B. (Methods of Information in Medicine, 2000)
In 1999, the Internet has become a major source of health information. The objective of CISMeF is to catalogue and index the main French-speaking health resources. In September 1999, the number of indexed resources totaled over 7,100 with a mean of 75 new sites per week. CISMeF uses two standard tools for organizing information: the Medline bibliographic database MeSH thesaurus and the Dublin Core metadata format. Resources included in CISMeF are described by the following: title, author or creator, subject and keywords, description, publisher, date, resource type, format, identifier, and language. To index resources, CISMeF uses five levels of hierarchy: “meta-term”, category, keyword, subheading, and resource type. CISMeF contains a thematic index, including medical specialities and an alphabetic index. CISMeF respects the Net Scoring, criteria to assess the quality of health information on the Internet. The CISMeF project offers a valuable tool for the French-speaking health community: 2,500 computer users visit the Web site each working day.
Keywords: Abstracting; Indexing; Catalogue; Internet; Vocabulary